Continuous Professional Development and Avoiding the Vanity Trap: an exploration of coaches’ lived experiences of supervision - Liz McGivern (International Journal of Evidence Based Coaching and Mentoring, 2009)
This research reported in this paper set out to explore and understand the lived experiences of coaches in supervision and captures the views they have formed as a result of their experience. It was discovered that there is a clear link between supervision and the continuous professional development experienced by participants. What also emerged is a view about a set of conditions that needed to be met for participants to have the confidence to open up their practice to scrutiny. A phenomenological methodology was used in order to explore participants experience and views. Participants’ verbatim comments are used to present the findings from which emerged four key themes. These themes underpin much of what the literature espouses with regard to efficacy of reflective practice and continuous professional development.